A Single Light-Responsive Sizer Can Control Multiple-Fission Cycles in Chlamydomonas - Heldt, Frank S.; Tyson, John J.; Cross, Frederick R.; Novák, Béla (Current biology, 2020)
Most eukaryotic cells execute binary division after each mass doubling in order to maintain size homeostasis by coordinating cell growth and division. By contrast, the photosynthetic green alga Chlamydomonas can grow more than 8-fold during daytime and then, at night, undergo rapid cycles of DNA replication, mitosis, and cell division, producing up to 16 daughter cells. Here, we propose a mechanistic model for multiple-fission cycles and cell-size control in Chlamydomonas. The model comprises a light-sensitive and size-dependent biochemical toggle switch that acts as a sizer, guarding transitions into and exit from a phase of cell-division cycle oscillations. This simple “sizer-oscillator” arrangement reproduces the experimentally observed features of multiple-fission cycles and the response of Chlamydomonas cells to different light-dark regimes. Our model also makes specific predictions about the size dependence of the time of onset of cell division after cells are transferred from light to dark conditions, and we confirm these predictions by single-cell experiments. Collectively, our results provide a new perspective on the concept of a “commitment point” during the growth of Chlamydomonas cells and hint at intriguing similarities of cell-size control in different eukaryotic lineages. [Display omitted] •G1 sizer and S/M oscillator can give rise to multiple fission in Chlamydomonas•A light-responsive bistable switch could guard transitions between G1 and S/M cycles•Light exposure increases the S/M-entry threshold, causing multiple-fission cycles•Lower S/M-entry threshold in the dark allows small cells to execute fewer divisions Heldt et al. present a quantitative model for multiple-fission cycles in Chlamydomonas reinhardtii, suggesting that a bistable sizer mechanism controls entry into and exit from cell-cycle oscillations.